Do adolescents need a rubella vaccination campaign? Rubella serosurvey among healthy children in Hangzhou, China - Wang, Xiaozhen; Xu, Yuyang; Zhang, Xuechao; Zhang, Xiaoping; Du, Jian; Che, Xinren; Gu, Wenwen; Wang, Jun; Jiang, Wei; Liu, Yan (Human vaccines & immunotherapeutics, 2023)
The aim of this study was to evaluate the seroprevalence of rubella antibodies and factors associated with antibody seropositivity after vaccination among healthy children aged 14 and below. A multi-stage stratified random sampling method was employed to recruit participants for the rubella serological test. An enzyme-linked immunosorbent assay method was used to detect human IgG antibodies with avidity for rubella virus in the sera of participants. Univariate and multivariate analyses were used to analyze associations between variables. A total of 778 subjects were included in the subsequent analysis. The overall positive rate of rubella antibody was 83.0% (95%CI: 80.2-85.5%), and the overall geometric mean concentration (GMC) was 58.05 IU/ml. In multivariate analysis, gender, residence, birth year group, and time since the last rubella-containing vaccines (RCV) vaccination were significantly associated with the seroprevalence of rubella antibodies. Our study showed a decreasing trend in rubella antibody positivity and GMC in the population aged five to 14 years. Therefore, we recommend a catch-up dose of RCV for adolescents and young people aged over 14 years not yet vaccinated.